The Edward Said reader - Said, Edward W.; Bayoumi, Moustafa; Rubin, Andrew (New York : Vintage Books, 2000)
Presents key selections from the works of Edward Said.
Introduction / Moustafa Bayoumi and Andrew Rubin -- Pt. I: Beginnings. The claim of individuality (1966) ; The Palestinian experience (1969) ; Molestation and authority in narrative fiction (1971) -- Pt. II: Orientalism and after. Orientalism (1978) ; Introduction to orientalism (1978) ; The scope of orientalism (1978) ; Zionism from the standpoint of its victims (1979) ; Islam as news (1980) ; Traveling theory (1982) ; Secular criticism (1983) ; Permission to narrate (1984) ; Interiors (1986) ; Yeats and decolonization (1988) -- Pt. III: Late styles. Performance as an extreme occasion (1989) ; Jane Austen and empire (1990) ; Intellectual exile: expatriates and marginals (1993) ; The Middle East'peace process': misleading images and brutal actualities (1995) ; On writing a memoir (1990) -- Pt. IV: Spoken words. An interview with Edward W. Said (1999)
'A Vintage Books original'--Title page verso.
Includes bibliographical references (pages 445-470)
Keywords: Said, Edward W; Politics and literature; Politics and culture; Criticism -- Political aspects; Aufsatzsammlung